The problematic of fiction in the narrative of Ventura García Calderón - Anchante Arias, Jim Alexander (2021)
Ventura García Calderón’s Peruvian narrative, inscribed in the aesthetic-literary context of modernist Indianism, generated a great controversy in its relationship with the political-cultural project of Indigenism in the first decades of the twentieth century in our country. This article seeks to reflect on this debate, focusing on some stories from his book La venganza del cóndor (1924), of the narrative scope of this author around the fantastic and the wonderful, as well as his unique position around the indigenist project.